2011
DOI: 10.1016/j.yjmcc.2010.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Paracrine mechanisms of stem cell reparative and regenerative actions in the heart

Abstract: Stem cells play an important role in restoring cardiac function in the damaged heart. In order to mediate repair, stem cells need to replace injured tissue by differentiating into specialized cardiac cell lineages and/or manipulating the cell and molecular mechanisms governing repair. Despite early reports describing engraftment and successful regeneration of cardiac tissue in animal models of heart failure, these events appear to be infrequent and yield too few new cardiomyocytes to account for the degree of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
323
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 433 publications
(332 citation statements)
references
References 120 publications
5
323
0
4
Order By: Relevance
“…Nevertheless, their precise cellular mechanisms still remain unclear [26,27] possibly because of the heterogeneity of the consisting cell populations of the sheet with various lineages or differentiation stages. How can we achieve a more profound elucidation of the mechanism, which is hampered due to the heterogeneity of the transplanted cells?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, their precise cellular mechanisms still remain unclear [26,27] possibly because of the heterogeneity of the consisting cell populations of the sheet with various lineages or differentiation stages. How can we achieve a more profound elucidation of the mechanism, which is hampered due to the heterogeneity of the transplanted cells?…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical trials and preclinical reports have demonstrated that intracoronary or intramyocardial injection of bone marrow (BM)-derived cells (hematopoietic stem/progenitor cells, mesenchymal stem cells, and endothelial progenitor cells) [9][10][11][12][13][14], skeletal myoblasts [15,16], or cardiac stem/ progenitor cells [17,18] ameliorate cardiac function following acute and chronic myocardial infarction (MI), even though there is still a deficiency in conclusive results for a full-scale therapy [19][20][21]. There seems to be little differentiation of transplanted stem cells into mature cardiovascular cell types, suggesting paracrine effects of transplanted cells in which humoral factors favorably affect the injured myocardium, including angiogenesis, apoptosis prevention, and promotion of healing [18,[22][23][24][25][26][27]. Nevertheless, as previous studies are consequences of injections of heterogeneous cell populations, insights to the cellular and molecular behavior and mechanisms after cell transplantation are still restricted.…”
Section: Introductionmentioning
confidence: 99%
“…Nguyen et al showed that the injection of MSC-derived factors (MDFs) achieved protection by paracrine eff ects rather than direct cardiac regeneration in a swine model of myocardial infarction (Nguyen et al, 2010). The array of potential therapeutic mechanisms off ered by MDFs includes antiapoptotic (Shabbir et al, 2009), anti-inflammatory (Bartosh et al, 2010, antifi brosis (Mirotsou et al, 2011), angiogenic (Kinnaird et al, 2004 and also regenerative eff ects. The intricacy of such factors in vivo has been also illustrated by Lee et al in a model in which the reduced size of myocardial infarction in response to the infusion of human MSCs was due to the secretion of the anti-infl ammatory protein (TSG-6), triggered by the entrapment of MSCs in the lung .…”
Section: Msc Paracrine Factors In the Repair Mechanismmentioning
confidence: 99%
“…Secretome of Messenchymal stem cells consists of cytokine, micro RNA (miRNA), exosomes and microvesicle which can cause therapy effect 5 and this is not because of cell differentiation 6 . Mechanism taken from secretome includes antiapoptosis 7 , anti-inflammation 8 , antifibrosis 9 , angiogenic 10 and the effect of tissue regeneration. The role of IL-10 is to promote autoantibodyproduction and autoreactive proliferation B cell.…”
Section: Introductionmentioning
confidence: 99%